NANOBIOPESTICIDES IN POST-HARVEST MANAGEMENT OF INSECT PESTS OF CROPS: PRESENT STATUS, CHALLENGES AND PROSPECTS – A REVIEW (FUDMA JOURNAL OF SCIENCES, 2024)
The major universal challenge on our planet is the issue of establishing food security for a rapidly increasing population in the world. Farmers all over the world focus on using new innovations and technologies for enhancing the production and storage of crops through intensive and extensive agriculture. The current efforts lead to the formation of nanopesticides and nanobiopesticides (NBPs) which has been made possible by advances in nanotechnology. Nanotechnology is one of the promising areas to boost the availability of food and to manufacture newer products for beneficial purposes in agriculture, food, water, the environment, medicine, energy, and electronics.NBPs are made using a variety of surfactants, polymers, nanoemulsions, nanocapsules, and metal nanoparticles with sizes in the nanometer range. These NBPs with an elevated surface-to-volume ratio are able to target organisms more effectively and persistently than traditional pesticides because of their physical characteristics and may continue to be effective for longer periods of time. In comparison to conventional pesticides, NBPs have the potential to improve the environment by decreasing toxicity, extending the shelf life of agricultural produce with the aid of nanoparticles, and enhancing the solubility of pesticides that are poorly soluble in water. However, the commercialization of NBPs faces significant obstacles due to their applicability in real-world settings, legal compliance, and market acceptability. Enhancing the usage and spread of NBPs are beneficial in reducing the number of spread chemicals, minimize nutrient losses in fertilization, and increased yield through pest and nutrient management.
Keywords: Delivery system; Eco-friendly; Micro-organism; Nanotechnology; Nanometer; Sustainability